К вопросу о функциональном значении извитости интраорганных нервов суставов - Ильенко, Н.Н. (Вестник зоологии, 1973)
The contortion degree of nerve stems and some nerve fibres in different components -of joints is determined by the degree of these components stretching. Nerve contortion is an important evolutionary acquirement of adaptive character. It plays the role of pro¬tective adjustment preserving nerves from rupturing when the tissue they innervate is strongly stretched.